Critical Analysis of the Problems of Education in Pakistan: Possible Solutions - Iqbal Ahmad; Kahil ur Rehman; Asghar Ali; Itbar Khan; Fazal Akber Khan (Institute of Advanced Engineering and Science, 2014)
Education lays the foundation for political, social and economic development of any country. A viable education system enables the nation to achieve its national goals. Pakistan as a developing country has faced critical problems of education since its inception and therefore, the system of education has failed to deliver according to the aspirations of the nation. There are various factors responsible for this situation. This paper explores some of the critical problems that have so far plagued the education system of Pakistan. On the basis of critical review of available literature, the paper presents solutions to the existing problems of the education system of Pakistan.DOI: http://dx.doi.org/10.11591/ijere.v3i2.1805